Comparative Study of CNN-based Deep Learning Models for Animal, Digit, and Flower Image Classification - Suri, Puti Andam; Setiono, Michael Alvin; Andrew, Andrew; Fajar, Muhammad (Engineering, MAthematics and Computer Science Journal (EMACS), 2025)
This study explores how four convolutional neural network (CNN) models MobileNetV2, DenseNet121, EfficientNetB0, and InceptionV3 perform in classifying images from three different datasets: animals, handwritten digits (MNIST), and flowers. The main goal is to understand which model offers the best balance between accuracy and efficiency when applied to datasets with varying complexity. Each model was trained and tested using identical preprocessing steps, and its performance was evaluated based on accuracy, precision, recall, and F1-score through a confusion matrix. Training and testing times were also measured to assess computational efficiency. The results show that DenseNet121 consistently achieved the highest accuracy: 98% on animal images and 88% on flower images, while MobileNetV2 provided a close performance (97% and 82%) but with much faster processing times, between 11 and 55 minutes. EfficientNetB0, on the other hand, performed poorly on the more complex flower dataset, achieving only 5% accuracy. These findings suggest that DenseNet121 is ideal for projects where accuracy is the main concern, whereas MobileNetV2 is more suitable for real-time applications that require quick responses without a major drop in accuracy. Overall, this research highlights the importance of aligning model selection with both dataset characteristics and computational limitations in practical image classification tasks.